Kinerja Protokol Distance Routing Effect Algorithm for Mobility (DREAM) Terhadap Serangan Wormhole pada Mobile Ad-hoc Network (MANET) - Prasetyo Eko Yulianto; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Mobile Ad-hoc Network (MANET) is a network consisting of a collection of mobile nodes that function as routers for data transmission. The node communicates without relying on a fixed network infrastructure. One of the routing protocols on the network is DREAM which has characteristics in finding paths using the routing table. Mobile nodes are free to join and leave the networks at any times, thus leaving MANET vulnerable to attack. One of them is a wormhole attack that creates a link between two or more of nodes that affects routing performance. The study will be conducted using NS-2.35 to see the performance of the DREAM protocol in the presence of a wormhole attack based on the scenario of the number of nodes and variation of the wormhole node with a random waypoint mobility and random direction model. Parameters for testing include packet delivery ratio (PDR), end-to-end delay, routing overhead, and convergence time. The results show that increasing the number of node variations can affect evaluation metrics, while increasing the number of wormhole nodes is more stable. Testing with 3 pairs of wormhole nodes get the lowest packet delivery ratio of 11.975 % on 10 nodes with random direction mobility. The highest end-to-end delay result is 446,544 ms at 50 nodes with random direction mobility. The highest routing overhead result is 33.216% at 50 nodes with random waypoint mobility, and the highest convergence time result is 183,459 s at 50 nodes with random waypoint mobility.